UTILIZING TOTAL DISSOLVED SOLIDS (TDS) SENSOR FOR DISSOLVED SOLIDS MEASUREMENT IN THE WATER - Zukhruf Z, Handandi; Elmi, Hidayana; Edy, Setiawan; Juniani, Anda Iviana; Anggara T, Nugraha; Amelia, P. (JISO : Journal of Industrial and Systems Optimization, 2024)
Although industrialization and population growth seriously threaten clean water, which is necessary for life, they also cause significant pollution. Monitoring water quality, including Total Dissolved Solids (TDS), ensures health standards. TDS represents dissolved substances in water, affecting taste, safety, and usability. Recent sensor advancements, particularly TDS sensors, offer real-time, cost-effective monitoring. This study evaluates the effectiveness of the TDS sensor in measuring dissolved solids, aiming to improve water quality monitoring methods. Results show that TDS sensors accurately distinguish between clean and dirty water, with an average error of 0.008894%. Future research should test sensor reliability in various conditions and enhance its technology. Water quality testing based on dissolved solids measurements in parts per million (PPM) indicates that 7 out of 12 samples meet clean water criteria, while others are dirty. Air bersih sangat penting untuk menopang kehidupan, tetapi semakin terancam oleh faktor-faktor seperti pertumbuhan populasi dan industrialisasi, yang menyebabkan polusi yang signifikan. Memantau kualitas air, termasuk Total Padatan Terlarut (TDS), sangat penting untuk memastikan standar kesehatan. TDS mewakili zat terlarut dalam air, yang memengaruhi rasa, keamanan, dan kegunaan. Kemajuan sensor terbaru, khususnya sensor TDS, menawarkan pemantauan waktu nyata dan hemat biaya. Penelitian ini mengevaluasi efektivitas sensor TDS dalam mengukur padatan terlarut, yang bertujuan untuk meningkatkan metode pemantauan kualitas air. Hasil penelitian menunjukkan bahwa sensor TDS secara akurat membedakan air bersih dan air kotor, dengan rata-rata kesalahan 0,008894%. Penelitian di masa depan harus menguji keandalan sensor dalam berbagai kondisi dan meningkatkan teknologinya. Pengujian kualitas air berdasarkan pengukuran padatan terlarut dalam satuan part per million (PPM) menunjukkan bahwa 7 dari 12 sampel memenuhi kriteria air bersih, sementara yang lainnya dikategorikan sebagai air kotor.